Maintaining Functional Islets through Encapsulation in an Injectable Saccharide-Peptide Hydrogel - Liao, Sophia W. (2013)
Islet transplantation offers a promising treatment for type 1 diabetes (T1D). However, a major hurdle in this treatment is the rapid loss of functional islets during culture and after transplantation. The liver site, currently utilized for transplantation, is suboptimal for achieving long-term insulin independence due to a rapid islet loss followed by a chronic decline in islet function after transplantation. Herein, we report a synthetic saccharide-peptide (SP) hydrogel that allows suspending islets in liquid and injecting for in situ polymerization without forming islet clumps, indicating its potential in extrahepatic islet transplantation. In vitro, rat islets in SP hydrogel maintained a 3D structure and high glucose-stimulated insulin release similar to that observed in freshly isolated islets for 4 weeks, while control islets cultured in suspension lost their 3D structure and insulin release responses by 2 weeks. Biocompatibility of SP hydrogel was shown by the absence of cytokine mRNA activation in peripheral blood mononuclear cells (PBMC) exposed to hydrogel in vitro and by the absence of cellular infiltrates in and around the hydrogel implanted subcutaneously. Syngeneic Lewis rat islets transplanted in SP hydrogel in various extrahepatic sites stained strongly for insulin, and more effectively reversed diabetes than unencapsulated islets when transplanted in an omental pocket. In conclusion, the SP hydrogel is non-cytotoxic and supports normal islet structure and function both in vitro and in vivo. Specifically, the ability of the hydrogel to separate individual islets after transplantation is important for maintaining their function in vivo. This important property, combined with the versatility and biocompatibility, makes our SP hydrogel a promising synthetic scaffold that can facilitate transplantation of organized heterogeneous cells to preserve their micro-structure and function.